2017
DOI: 10.1080/21548331.2017.1303326
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on non-drug related poisoning in the community among children from south India

Abstract: This study for the first time gives an elaborative insight on non-drug related pediatric poisoning from a tertiary care center in south India for almost a decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…In a study conducted by das Adhikari et al, 62.79% were male. [2] Similar results were obtained in a study conducted by Reddy et al, where 53.1% were male. [11] However, the study conducted by Sahin et al reported that the majority were female (51.6%).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In a study conducted by das Adhikari et al, 62.79% were male. [2] Similar results were obtained in a study conducted by Reddy et al, where 53.1% were male. [11] However, the study conducted by Sahin et al reported that the majority were female (51.6%).…”
Section: Discussionsupporting
confidence: 85%
“…Similar distribution was also seen in a study conducted by Das Adhikari et al, where 77.42% of children were below the age of 5 years, which seem to be in line with the study done by Reddy et al, where 70.4% were within the age group of <5 years. [2] The study conducted by Agarwal et al also reiterated this point with the majority of children belonging to 1-3year age group. [3] Hence, children younger than 5 years in India are vulnerable age for poisoning.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…1 , [3][4][5] The morbidity and mortality associated with such poisoning in children are primarily related to the pulmonary aspiration and its subsequent complications. 6 The inflammatory reaction in the lungs depends on the degree of exposure, volatility, and viscosity of the particular hydrocarbon. Among hydrocarbons, those with low viscosity and surface tension, such as, kerosene, lighter fluid, lamp oil, and naphtha, are frequently associated with clinically significant effects on the respiratory system.…”
Section: Introductionmentioning
confidence: 99%